Lithospheric-scale folding in Iberia from the perspective of analogue modelling - Fernández-Lozano, J.; Sokouties, D.; Willingshofer, E.; De Vicente, G.; Cloetingh, S. (TRABAJOS DE GEOLOGÍA, 2009)
The Iberian Peninsula is characterized by the presence of regularly spaced and generally E-W to NE-SW trending mountain ranges with mainly E-W crustal-scale thrusts across the whole Peninsula. Intraplate deformation resulting from the convergence between the African and European plates during the Tertiary caused a regular distribution of the main topographic heights and is often related to lithospheric buckling. Consequently, basement structures were reactivated as fault corridors coeval with inversion of the Mesozoic rifts. For gaining insights into the effects of different crustal and mantle rheologies, on the structural and topographic expression of lithospheric buckling, the analogue modelling approach has been employed. Varying the shortening velocity and, hence, the strength of the ductile layers demonstrate that high strength of the ductile crust and upper ductile mantle leads to an increase in lithospheric fold wavelength(s). The folding is associated with the formation of narrow mountain ranges, which are represented by upper crustal pop-ups forming the main topographic reliefs. Shortening is accommodated within the viscous crust underneath the pop-ups by homogeneous thickening leading to lateral thickness variations of the ductile crust. Such thickness variations are in agreement with seismic and gravity data from the Spanish Central System and Toledo Mountains. Experiments performed under low velocities (0.5 cm h-1, representing 7 mm a-1 in nature) show close similarities to the natural laboratory Iberia in terms of the general shape and distribution of mountain ranges and basins.